The Art of Maulid Ad-Diba' Between Tradition and Islam in the Archipelago from a Multicultural Education Perspective - Huda, Miftahul (Mimbar Agama Budaya, 2024)
Multicultural education developed during this period is not prioritized based on community traditions. This research aims to explain that the Islamic tradition of Mawlid Ad-Diba' art or Islamic teachings, Islamic traditions in the archipelago can be used as a basis for multicultural education and the values of multicultural education contained in the art of Mawlid ad-Diba'. This research method is library research with a phenomenological approach and using documentation techniques. The research results show 1) an Islamic tradition; 2) Islam in the archipelago is a form of Islamic moderation, 3) multicultural education based on Islamic traditions, 4) the values of multicultural education: spiritual, social, moral, and unity. The research concludes that the art of Maulid ad-Diba' is not an Islamic teaching in the archipelago but is an Islamic tradition and can be used as a basis for multicultural education that has the values of faith and piety, gratitude, humility, honesty, friendliness, fair, patient.